Professional Nursing Care Applied to The Individual Diagnosed with Crohn's Disease: A Case Report - Ilknur yücel (KHD Production, 2024)
Crohn's disease, which is one of the inflammatory bowel diseases, is an intestinal disease with acute exacerbations and can involve any part from the mouth to the anus. The objective of this case report was to prepare a nursing care plan for a patient diagnosed with 'Crohn's Disease' by using the nursing diagnoses in the North American Nurses Diagnosis Association (NANDA) classification system. The patient was a female, married, a high school graduate, and a 36-year-old housewife. The patient was diagnosed with Crohn's disease as a result of laboratory and radiologic imaging in a hospital where she applied with severe abdominal pain in 2006. The patient received medical treatment for about two years and overcame the attack period of the disease. On April 11, 2022, the patient went to the Emergency Department of a university hospital with abdominal pain and fatigue. The patient's detailed laboratory findings and radiologic imaging were obtained, and she was admitted to the Gastroenterohepatology Service. It is very important that quality health care services are provided to individuals with poor health status by nurses, who are among the leading health professionals. It was observed that planning the patient's care according to the North American Nurses Diagnosis Association (NANDA) Classification System and analyzing the data according to the sub-dimensions of the model provided quick solutions for the patient's problems and systematic nursing care for the patient.